Differential Agar Medium for Separating Streptococcus lactis and Streptococcus cremoris - Reddy, M. Srinivasulu (1969)
The characteristic ability of Streptococcus lactis and inability of Streptococcus cremoris to hydrolyze arginine formed the basis for the development of a differential agar medium to separate these species in pure and mixed cultures. Ammonia liberated from arginine was detected by the pH changes occurring in the medium. The agar contained milk as the sole source of carbohydrate, arginine as the specific substrate, diffusible (K(2)HPO(4)) and nondiffusible (CaCO(3)) buffer systems, and a suitable pH indicator in addition to other ingredients. The nondiffusible buffer system afforded the localization of pH changes, and, hence, the indicator color changes immediately around individual colonies appearing on the medium. S. cremoris produced yellow colonies surrounded by yellow zones on this purple medium because of their ability to produce acid from lactose in the milk. S. lactis, on the other hand, first produced colonies similar to S. cremoris, but subsequent color reversal of pH indicator with the liberation of NH(3) resulted in the discharge of the yellow color. Hence, S. lactis colonies were white and devoid of zones. The difference in their colony color allowed the identification of the species in a mixture of S. cremoris and S. lactis strains. The medium was found suitable for both qualitative and quantitative differentiation.